2008
DOI: 10.1371/journal.pone.0003191
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of HIV-1 Subtypes in Nairobi, Kenya

Abstract: BackgroundGenetic analysis of a viral infection helps in following its spread in a given population, in tracking the routes of infection and, where applicable, in vaccine design. Additionally, sequence analysis of the viral genome provides information about patterns of genetic divergence that may have occurred during viral evolution.ObjectiveIn this study we have analyzed the subtypes of Human Immunodeficiency Virus -1 (HIV-1) circulating in a diverse sample population of Nairobi, Kenya.Methodology69 blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…Samples with bands obtained at 150bp were considered positive. To determine the quality of amplification of the extracted tumor DNA, β-globin PCR was performed(20). …”
Section: Methodsmentioning
confidence: 99%
“…Samples with bands obtained at 150bp were considered positive. To determine the quality of amplification of the extracted tumor DNA, β-globin PCR was performed(20). …”
Section: Methodsmentioning
confidence: 99%
“…The region is also characterized by a very heterogeneous epidemic. Uganda and Kenya show a predominance of subtype A and D [12], [13], [14]. In Burundi, the epidemic is largely due to subtype C [15] while subtype A and C predominate in Tanzania [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous molecular epidemiological studies done in Kenya mostly used samples from Nairobi. [4][5][6][7][8][9] A few other studies also investigated southern, 10 northern, 11 and western Kenya, 12 as well as the coastal region. 13,14 All of these studies indicated that HIV-1 subtype A is the most common subtype in Kenya, but that subtypes C, D, G, and recombinant forms were also detected.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 All of these studies indicated that HIV-1 subtype A is the most common subtype in Kenya, but that subtypes C, D, G, and recombinant forms were also detected. [4][5][6][7][8][9][10][11][12][13][14] The complexity of HIV-1 diversity creates major challenges for vaccine design and development strategies. More than one HIV-1 vaccine candidate based on HIV-1 subtype A has been evaluated in Kenya during Phase I and II clinical trials.…”
Section: Introductionmentioning
confidence: 99%